Innovation Performance: What Is Happening In Agricultural Cooperatives? - Heloiza Cristina Holgado-Silva; Erlaine Binotto (BBR: Brazilian Business Review)
Studies have pointed to gaps in the understanding of innovation performance in the industrialization of cooperatives. This paper has addressed the innovation performance of Brazilian agricultural cooperatives in economic-financial and social dimensions. For our research, we conducted a semi-structured interview with managers of cooperatives that adopted the industrialization of products. In the economic-financial dimension, cooperatives increased the offer/variety of products and gained new markets, while, in the social dimension, the industrialization of new products for the cooperative, or for the market. These may affect the sense of pride in belonging to the cooperative due to the availability of a manufactured product for purchase that resulted from the commodity produced by the cooperative members. This study improves the understanding about the innovation performance model, and shows how cooperatives have addressed this topic. Such an understanding can assist in the development of strategies for innovation in cooperatives. The findings contribute to the understanding of innovation in industrialization, and add efforts in research on innovation in emerging economies.